2015
DOI: 10.1002/uog.14759
|View full text |Cite
|
Sign up to set email alerts
|

Stomach position in prediction of survival in left‐sided congenital diaphragmatic hernia with or without fetoscopic endoluminal tracheal occlusion

Abstract: Objective To investigate the value of fetal stomach position in predicting postnatal outcome in left-sided congenital diaphragmatic hernia (CDH) with and without fetoscopic endoluminal tracheal occlusion (FETO). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 35 publications
4
78
4
Order By: Relevance
“…Data from a proportion of cases presented in this study were reported in two previous collaborative studies [8,9] .…”
Section: Methodsmentioning
confidence: 99%
“…Data from a proportion of cases presented in this study were reported in two previous collaborative studies [8,9] .…”
Section: Methodsmentioning
confidence: 99%
“…However, their proposed algorithm requires particular expertise in fetal evaluation of left CDH: the determination of liver position and judgment as to the degree of abnormality of the herniated stomach [12, 25, 26]. Cordier and colleagues recently demonstrated that fetal stomach position was predictive of postnatal survival and need for prosthetic patch repair of the diaphragm defect [21]. However, to our knowledge, the relationship between fetal stomach position, neonatal extracorporeal membrane oxygenation (ECMO) requirement, and short-term respiratory morbidity has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The intra-abdominal fetal stomach position is associated with a more favorable prognosis, whereas the presence of the stomach within the thorax during the fetal or neonatal period has been shown in multiple studies to correlate with an adverse outcome. Recently, Cordier et al have confirmed that fetal stomach position was predictive of postnatal survival and the need for patch repair [25]. According to some papers, there might be a strong association between neonatal death, ECMO (extracorporeal membrane oxygenation) requirement and short-term respiratory morbidity, depending on the position of the fetal stomach [24].…”
Section: Prognostic Factorsmentioning
confidence: 95%